MENGANALISIS DAN PERANCANGAN E-BUSINESS DALAM POTENSI PERTUMBUHAN USAHA BUDIDAYA IKAN HIAS DISCUS SURABAYA 88 - Citra Firnanda Zalianty; Ari Susanto (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
The growth of the ornamental fish breeding industry, particularly in Discus Surabaya 88, has demonstrated significant potential in recent years. The development of information technology, especially the internet, has presented new opportunities for businesses in this sector. This research aims to analyze and design the implementation of an e-business model that can expedite the growth of Discus Surabaya88's. This research employs a qualitative approach by interviewing owners of ornamental fish stores who have integrated e-business into their operations. The data collected are analyzed using content analysis to identify the advantages and challenges faced by these business stakeholders. The research findings reveal that the adoption of e-business in Discus Surabaya88's offers numerous benefits. Firstly, e-business enables businesses to reach a wider market through online marketing and global market penetration. Secondly, e-business allows businesses to improve operational efficiency by automating sales, payments, and deliveries. Thirdly, e-business empowers businesses to access real-time market information, facilitating more precise decision-making in product development and business strategies. Nonetheless, businesses encounter certain challenges when implementing e-business in the context of Discus Surabaya88's. The primary challenge is limited internet access, which can affect connectivity and accessibility for businesses in remote areas. Additionally, ensuring online transaction security and safeguarding customer data is a critical issue that must be addressed effectively. This research designs an e-business model that can be implemented within Discus Surabaya88's. This model encompasses aspects of online marketing, transaction management, customer data administration, as well as information security.